Cover Picture: Ammonothermal Synthesis and Characterization of Cs2[Zn(NH2)4] (Z. Anorg. Allg. Chem. 21/2016). Issue 21 (October 2016) - Richter, Theresia M. M.; Alt, Nicolas S. A.; Schlücker, Eberhard; Niewa, Rainer
Abstract : The cover picture shows the [Zn(NH2 )4 ] 2− ion in front of a several cm large crystal aggregate of Cs2 [Zn(NH2 )4 ] obtained from supercritical ammonia in a temperature gradient. Such compounds are speculated to serve as soluble intermediates in a conceivable ammonothermal growth of zinc nitride crystals under ammonobasic conditions, as similar appears in the ammonothermal GaN crystal growth. More details can be found in the article by Rainer Niewa et al on page1207 ff .